2014
DOI: 10.1371/journal.pone.0111352
|View full text |Cite
|
Sign up to set email alerts
|

MBP-Positive and CD11c-Positive Cells Are Associated with Different Phenotypes of Korean Patients with Non-Asthmatic Chronic Rhinosinusitis

Abstract: BackgroundAsthmatic nasal polyps primarily exhibit eosinophilic infiltration. However, the identities of the immune cells that infiltrate non-asthmatic nasal polyps remain unclear. Thus, we thought to investigate the distribution of innate immune cells and its clinical relevance in non-asthmatic chronic rhinosinusitis (CRS) in Korea.MethodsTissues from uncinate process (UP) were obtained from controls (n = 18) and CRS without nasal polyps (CRSsNP, n = 45). Nasal polyps (NP) and UP were obtained from CRS with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…Because the presence of atopy and smoking history may affect CRS endotype, stratified analyses were performed on the age‐related changes of each CRS subtype. In the ENP groups, the age‐related changes in inflammatory mediators consistently demonstrated that type 3 (IL‐17A) and type 1 (IFN‐γ) increased with ageing, irrespective of atopy status or smoking history (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Because the presence of atopy and smoking history may affect CRS endotype, stratified analyses were performed on the age‐related changes of each CRS subtype. In the ENP groups, the age‐related changes in inflammatory mediators consistently demonstrated that type 3 (IL‐17A) and type 1 (IFN‐γ) increased with ageing, irrespective of atopy status or smoking history (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…A diagnosis of asthma was performed by an allergist based on medical history and lung function analysis, including methacholine challenge tests. Nasal polyps (NPs) were classified into two groups: eosinophilic NP, which was defined as having an eosinophil count of more than 10% of the inflammatory cell population, and non-eosinophilic NP, which did not fulfil this criterion 24. Additional information and details of the subjects' characteristics are listed in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA levels in UP and NP tissues were evaluated using quantitative real-time (qRT)-PCR analysis as previously described 24. Detailed qRT-PCR conditions are described in the Methods section in the Online Repository (http://www.thorax.bmj.com).…”
Section: Methodsmentioning
confidence: 99%
“…Among these signs, tissue eosinophilia is the most important regarding disease recurrence and comorbidities 7. Approximately 70%-80% of CRSwNP cases accounts for eosinophilic types in the Western country, whereas 30%-40% cases constitute eosinophilic NP in Asian countries, including South Korea and China 29. Eosinophilic CRS is a better responder to steroid therapy vs non-eosinophilic CRS 67.…”
Section: Personalized Therapeutic Strategiesmentioning
confidence: 99%
“…However, there are no standard methods to evaluate tissue eosinophilia due to uneven distribution throughout the tissue 8. Multiple inflammatory cells exist in most NP tissue, but the function and pathological roles of these cells are not yet completely elucidated 9. Even in eosinophilic NP, neutrophils and macrophages exist and may play a role in nasal polypogenesis 2.…”
Section: Introductionmentioning
confidence: 99%